Tinjauan Yuridis Akibat Perceraian terhadap Pembagian Harta Gono-Gini Menurut Kitab Undang-Undang Hukum Perdata pada Putusan Nomor : 706/Pdt.G/2012/PN.Medan - Simatupang, Binka Lg; Siregar, Taufik (Universitas Medan Area, 2017)
Juridical Review Due to Divorce Against Gono-Gini Property Distribution According to the Civil Code on Decision Number: 706/Pdt.G/2012/PN.MedanThe main goal of humans in slimming is to form a harmonious household. Based on the marriage law number 1 of 1974, marriage is a birth bond between a man and a woman as a husband with a family (household) goal that is pleasant or eternal through the Almighty Godhead. If the divorce occurs indoors, the household can be described as having a result of the person in dispute in the household, where during the marriage, the household that has assets or in everyday language in Indonesia is said to be a